Japan : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Japan. (IMF Staff Country Reports; Country Report, 2018)
The rapid aging and shrinking of Japan's population will dominate economic policy making in coming decades-impelling a fresh look at the objectives and tools of Abenomics. Six years of Abenomics have yielded some important results, but achieving sustained high growth and durable reflation, while also tackling debt sustainability and a shifting global economic landscape, will require strengthened policies.